AI: Analyzation of Human-Robot relationship and Role of Nanotechnology in the Selected movies Enthiran (Robot) and Ra.One - Kaur, Jasmeen (Journal of Neonatal Surgery, 2025)
The research paper analyzes the relationship between humans and Robots and functioning of artificial emotions with the use of AI through the movies Enthiran (Robot) and Ra.One. It explores the impact of advanced nanotechnology, virtual reality, augmented reality and wireless technology in the real life. The research scrutinizes how the directors of the movies successfully converts virtual game into reality by using sensors and H.A.R.T which is more advanced level of gaming. The movies Enthiran (Robot) and Ra.one explore the creation of cognitive machines to examine the complex elements of artificial intelligence, autonomy and emotional intelligence. The movie Ra.One highlights how AI is served as protector and companion to the humans by analyzing the relationship between protagonist’s son and AI, Ga.One. The research paper acknowledges the role of nanotechnology for the composition of robots- Ra.One and Chitti in the respective movies. Nanotechnology helps to converts virtual characters of the game into the real world by enhancing the components of nanobots, nano swarm and nano suits